Identitas Budaya, Kreativitas, dan Kajian Arkeologi Publik - Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2009)
AbstractPublic Archaeology can’t be understood as a narrow-minded view point as an archaeological research and their object’s presentation and representation at the public only. However, public archaeology must be understood more widely as an archaeological view point for understand the public requirements and importance. These discipline have an important meaning for the socialization of supreme culture values at the past. On the future, those values will be reinforcing the national cultural identities from the foreign cultural influence. In order to those purpose, public role, active and seletive creativity in the foreign culture adoption without leaving any cultural identity, will be necessary.